The function of histone methyltransferase SETDB1 and its roles in liver cancer - Zhang, Enxiang; He, Pingping (Frontiers in Cell and Developmental Biology, 2024)
Epigenetic alterations in gene expression have been implicated in cancer development and tumor immune escape, with posttranslational histone or non-histone modifications representing attractive targets for disease surveillance and therapy. SET domain bifurcated 1 (SETDB1) is a histone lysine methyltransferase that reversibly catalyzes the di- and tri-methylation of histone 3 lysine 9 (H3K9) on euchromatin, inhibiting gene transcription within these regions and facilitating the switch from euchromatic to heterochromatic states. Emerging evidence suggests that SETDB1 amplification and aberrant activation are significantly associated with poor prognosis in hepatocellular carcinoma (HCC), and contribute to HCC development, immune escape, and immune checkpoint blockade (ICB) resistance. Here, we provide an updated overview of the cellular and molecular effects of SETDB1 activity in hepatocarcinogenesis and progression and focus on studies linking its function to immunotherapy for HCC, and present current challenges and future perspectives for targeting SETDB1 in HCC treatment.